PROJECT-BASED APPROACH AS AN INNOVATIVE FORM OF ORGANIZING COMPANY CRISIS MANAGEMENT - LOTOCKYI, Roman; RUDA, Liliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to a comprehensive study of the role of crisis management in ensuring stability and sustainable development of enterprises under the conditions of constant economic uncertainty and global turbulence. The authors emphasize that crisis phenomena are an inevitable component of modern business processes, and therefore the ability of a company to anticipate threats, adapt to dynamic changes, and maintain resilience becomes a key factor in its competitiveness. In this context, the article highlights the importance of implementing innovative management tools, with a particular focus on the project-based approach.The research examines modern principles of developing an effective anti-crisis strategy, including proactivity, flexibility, risk orientation, and adaptability. The project-based approach is presented as a methodological tool that allows managers not only to structure decision-making processes but also to ensure the coordination of resources, time, and human potential. This approach makes it possible to divide a complex anti-crisis strategy into manageable projects with clear goals, timeframes, and responsible executors. As a result, management processes become more transparent, controllable, and measurable.The article provides a conceptual framework for integrating the project-based approach into the crisis management system. The main stages are outlined: identification and assessment of risks, formation of possible response scenarios, selection of optimal solutions, monitoring of implementation, and adaptation of action plans depending on external and internal changes. At each stage, special attention is paid to communication and coordination between stakeholders, which helps to strengthen collective responsibility and trust within the organization.The advantages of the project-based approach are analyzed in detail. These include transparency of processes, increased managerial discipline, enhanced teamwork, and the ability to quickly adjust strategic and tactical priorities. The method also facilitates knowledge accumulation and transfer, creating a system of organizational learning that increases the company’s resilience in the long term. At the same time, the article does not ignore possible limitations. The authors note that the implementation of a project-based model requires significant resources, the involvement of highly qualified personnel, and the development of a project-oriented corporate culture. There is also the risk of excessive bureaucratization and formalization of processes, which may reduce the flexibility of management.The practical significance of the research lies in the fact that the proposed methodological approaches can be used by managers of different levels, consultants, business analysts, and academic staff in the field of economics and management. The results can serve as a basis for developing corporate anti-crisis programs, conducting training for managers, and implementing modern project management standards in companies.Thus, the article argues that the project-based approach is an effective and innovative tool for crisis management, which allows enterprises not only to respond to critical threats but also to transform challenges into opportunities for sustainable growth and long-term competitiveness.
Keywords: crisis management; management; enterprise; project; project-based approach; project management